2010
DOI: 10.1111/j.1600-079x.2010.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for the neuroprotective effect of melatonin against methamphetamine‐induced autophagy

Abstract: Methamphetamine (METH) is a common drug of abuse that induces toxicity in the central nervous system and is connected to neurological disorders such as Parkinson's disease. METH neurotoxicity is induced by reactive oxygen species (ROS) production and apoptosis. Moreover, autophagy is an alternative to cell death and a means for eliminating dysfunctional organelles. In other cases, autophagy can end up in cell death. Nonetheless, it is not clear whether autophagy is also correlated with apoptotic signaling in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 48 publications
7
82
0
Order By: Relevance
“…It has been shown that oestradiol reduced mRNA levels of the pro-apoptotic Bad in PC12 cells transfected with ERα (Gollapudi and Oblinger 1999). Nopparat et al (2010) have demonstrated, in the SK-N-SH dopaminergic cell line, a novel role of melatonin in protecting cells from autophagic cell death triggered by the Bcl-2/Beclin 1 pathway, by inhibiting the activation of the JNK1 (cJun amino-terminal kinase), Bcl-2 upstream pathway. Melatonin increased Bcl-2 and augmented expression of XIAP in ethanol-treated HN2-5 (mouse hippocampal neuron-derived) cells (Shetha et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oestradiol reduced mRNA levels of the pro-apoptotic Bad in PC12 cells transfected with ERα (Gollapudi and Oblinger 1999). Nopparat et al (2010) have demonstrated, in the SK-N-SH dopaminergic cell line, a novel role of melatonin in protecting cells from autophagic cell death triggered by the Bcl-2/Beclin 1 pathway, by inhibiting the activation of the JNK1 (cJun amino-terminal kinase), Bcl-2 upstream pathway. Melatonin increased Bcl-2 and augmented expression of XIAP in ethanol-treated HN2-5 (mouse hippocampal neuron-derived) cells (Shetha et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…42 It also has protective effects on methamphetamine-induced autophagic cell death in vitro. 48 We tested whether exogenous adding of melatonin could prevent MPTP-induced autophagy and cell death. As shown in Figure 3A and B, melatonin could restore the elevated CDK5 level induced by MPTP in C6 cells.…”
Section: Mptp Induced Cdk5-mediated Autophagy Leading To Death Of C6mentioning
confidence: 99%
“…A deficiency in the autophagy-related protein beclin1 modulates amyloid precursor protein accumulation and promotes neurodegeneration (207). Melatonin protects neurons against the Bcl2/Beclin1 autophagic cell death pathway by the activation of the JNK1/Bcl2 cascade (208) and modulates mTOR activity and 4E-BP1 phosphorylation (209).…”
mentioning
confidence: 99%